Advances in insect physiology. - Evans, P. D.; Wigglesworth, Vincent B. (Vincent Brian), Sir, 1899-1994 (Advances in insect physiology, 1988)
This latest volume in this series contains articles on a variety of insect physiological topics from the nervous system to the cuticle and circulatory system.